1989
DOI: 10.1086/337741
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Water Relations in the CAM Atmospheric Epiphyte Tillandsia usneoides L. (Bromeliaceae)

Abstract: Past studies have reported two unusual aspects of the water relations of the atmospheric CAM epiphyte Tillandsia usneoides L. (Bromeliaceae): a drought stimulation of nocturnal C0 2 uptake, and nocturnal absorption of water vapor. Contrary to past reports, a 10-d drought did not stimulate nocturnal C0 2 uptake in this species. On the other hand, previous reports of nocturnal water vapor absorption were confirmed in situ throughout a year, although tissue hydration from this source was insufficient to offset da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 8 publications
4
53
0
1
Order By: Relevance
“…The large changes in leaf water content reported for Tillandsia ionantha in this study are similar to those observed in the same species by Benzing and Dahle (1971) as well as those reported for Tillandsia usneoides (Martin and Schmitt 1989) and Tillandsia schiedeana (Martin and Adams 1987). Likewise, the water and osmotic potentials measured in T. ionantha throughout the imposed drought treatment are comparable to those reported for this species as well as for other epiphytic bromeliads in other studies (Harris 1918;Biebl 1964;Griffiths et al 1986;Liittge et al 1986;Smith et al 1986&).…”
Section: Comparisons Of Results With Previous Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…The large changes in leaf water content reported for Tillandsia ionantha in this study are similar to those observed in the same species by Benzing and Dahle (1971) as well as those reported for Tillandsia usneoides (Martin and Schmitt 1989) and Tillandsia schiedeana (Martin and Adams 1987). Likewise, the water and osmotic potentials measured in T. ionantha throughout the imposed drought treatment are comparable to those reported for this species as well as for other epiphytic bromeliads in other studies (Harris 1918;Biebl 1964;Griffiths et al 1986;Liittge et al 1986;Smith et al 1986&).…”
Section: Comparisons Of Results With Previous Studiessupporting
confidence: 91%
“…Despite quantitative differences in the results, the overall patterns of metabolic responses to drought stress observed in this study are remarkably similar to those reported for T ionantha by Benzing and Dahle (1971), as well as for other species of Tillandsia (Martin and Adams 1987;Martin and Schmitt 1989). Specifically, nocturnal C0 2 uptake rates were unaffected during the initial stages of drought stress (over a wide range of water contents), then decreased significantly after 20 d of the drought treatment.…”
Section: Comparisons Of Results With Previous Studiessupporting
confidence: 86%
See 3 more Smart Citations